A non-lethal stable isotope analysis of valued freshwater predatory fish using blood and fin tissues as alternatives to muscle tissue - Vejřík, Lukáš; Vejříková, Ivana; Sajdlová, Zuzana; Kočvara, Luboš; Kolařík, Tomáš; Bartoň, Daniel; Jůza, Tomáš; Blabolil, Petr; Peterka, Jiří; Čech, Martin; Vašek, Mojmír (PloS one, 2024)
Stable isotope analysis (SIA) is widely used to study trophic ecology and food webs in aquatic ecosystems. In the case of fish, muscle tissue is generally preferred for SIA, and the method is lethal in most cases. We tested whether blood and fin clips can be used as non-lethal alternatives to muscle tissue for examining the isotopic composition of two freshwater predatory fish, European catfish (Silurus glanis) and Northern pike (Esox lucius), species of high value for many freshwater systems as well as invasive species in many others. Blood samples from the caudal vein, anal fin clips, and dorsal muscle obtained by biopsy punch were collected from four catfish and pike populations (14-18 individuals per population). Subsequently, these samples were analyzed for δ13C and δ15N. The effects of alternative tissues, study site, and fish body mass on the isotopic offset were investigated. Both species showed a correlation between the isotopic offset and the tissue type, as well as the study site, but no significant relationship with the body mass. The isotopic offsets between tissues were used to calculate the conversion equations. The results demonstrated that both blood and fin clips are suitable and less invasive alternative to muscle in SIA studies focused on European catfish and Northern pike. Blood provided better correspondence to muscle isotope values. However, our results clearly demonstrated that isotopic offsets between tissues vary significantly among populations of the same species. Therefore, obtaining a muscle biopsy from several individuals in any population is advisable to gain initial insights and establish a possible population-specific inter-tissue conversion.
Keywords: izotopy dusíku; izotopy uhlíku; Catfishes; ekosystém; Muscles; Carbon Isotopes; Animals; Nitrogen Isotopes; svaly; sumci; sladká voda; Fresh Water; Ecosystem; zvířata; Esocidae